Determinants of Firm Leverage in Chile: Evidence from Panel Data - Fernández, Viviana (Estudios de Administración, 2005)
There is an extensive literature on the determinants of capital structure for developed countries, but little has been said about emerging economies. This article analyzes the driving forces of capital structure in Chile for the period 1990-2002. We study interest-bearing liabilities for firms classified by economic sectors. Our results give more support to the trade-off theory than to the pecking-order hypothesis. The contribution of our work is also methodological. Our econometric specification is based on a random-effects panel data model for censored data developed by Anderson (1986) and extended by Kim and Maddala (1992). We extend Anderson-Kim-Maddala’s work to panel data models for uncensored data, and devise specification tests for non-nested random-effects models. Most literature on capital structure focuses on the cross-section variation of the data by averaging observations over time.